A novel expandable drug-eluting ureteric stent for the treatment of urological disorder - Tan, Jun Xiang (Nanyang Technological University, 2020)
Ureteral stricture is one of the most common urologic condition. In this project, strictures caused by fibrosis or excessive accumulation of collagen due to scarring is explored. Fibrosis proliferation can be inhibited by an anti-inflammatory drug Dexamethasone (DEX). However, the true challenge is for drug penetration through urothelium of the ureter. A solution to this issue would be a second layer of swellable hydrogel, that after implantation, would swell upon contact with urine/ water and make direct contact with the urothelium. This will help promote better drug delivery to the ureter and prevent stricture recurrence. This project explores the fabrication and optimisation of Poly-L-Lactide-co-Caprolactone (PLC) coating at 10µm, 25µm, 40µm. Following that, we proceed to the coating of the stents at 2.5%, 5% and 7.5% DEX concentration at the above-mentioned thickness. We also study the stability of DEX, the effects of coating thickness and drug concentration on the drug release profile, as well as determine the daily drug dosage so it can be compared to the minimum effective concentration to determine if it is sufficient in inhibiting fibrosis proliferation. It was first determined that DEX is stable at 4°C and unstable at 37°C. This is important to consider as the 37°C is the average human body temperature and implantation of the stent into the body would subject the DEX to bodily conditions. Second, the coating optimization is performed at various PLC Concentration (0.3w/v%, 0.6w/v%, 0.9w/v%) over a series of different loop number (25, 50, 75, 150). After plotting the thickness data over the number of loops, it was immediately determined that 0.9w/v% PLC concentration was the most effective in giving a thicker coating with minimal loop number. Using the same data, the optimised loop number for obtaining 10µm, 25µm and 40µm at 0.9w/v% PLC concentration is determined at 30, 100 and 215 loops. Surface morphology of 0.9w/v% PLC concentration at 2.5% DEX, 5% DEX and 7.5% DEX was also observed and can be fully dispersed evenly throughout the entire polymer matrix. The in vitro drug release study showed that the loading efficiency of the DEX into a stent increases with increasing amount of drug present in the stent. The drug release study was conducted at several parameters. To compare the effect of coating thickness on drug release, stents with 0.9w/v% PLC concentration and 5% DEX at 10µm, 25µm and 40µm were used. It showed that with increasing thickness, the drug release was slower due to longer diffusion path length. For comparing the effect of DEX concentration on drug release, 0.9w/v% PLC concentration and 25µm coating thickness at 2.5% DEX, 5% DEX and 7.5% DEX was used. The results concluded that the higher the concentration of DEX, the slower the release of DEX due to the equation for fractional release stating that fractional drug released is inversely proportional to the initial drug concentration. Daily drug release data was also complied. This data showed the dosage of DEX released into the body and can be used to determine if the treatment is effective when compared with the minimum effective concentration of DEX to inhibit fibroblast proliferation. The release trend also showed that the drug released is a first order release with higher concentration released at the start, and the release rate decreases as time increases. In conclusion, this report focuses on the delivery of DEX straight to the site of action in the ureter for effective treatment of strictures and has optimised the coating parameters of PLC loaded with DEX. The release study was also successful is showing the how the coating thickness and DEX concentration effects the drug release over a period of 8 weeks. However, much more test needs to be done mainly in cell work to determine the minimum effective concentration of DEX as there are not any past studies conducted in this very specific area. The inclusion of a hydrogel layer with various surface medication also needs to be tested to determine the best adhesive method between the PLC and hydrogel layer. Drug release studies also need to be conducted to study the effects of surface medication on the drug release of DEX as well as the what effects the inclusion of a hydrogel layer would have on the drug release.